Local inflammation, lethality and cytokine release in mice injected with Bothrops atrox venom. Issue 5 (1998) - Barros, S. F.; Friedlanskaia, I.; Petricevich, V. L.; Kipnis, T. L.
Abstract : We have provided evidence that: (a) lethality of mice to crude Bothrops venom varies according the isogenic strain (A/J > C57Bl/6 > A/Sn > BALB/c > C3H/ HePas > DBA/2 > C3H/He); (b)BALB/c mice (LD50 =100.0 μg) were injected i.p. with 50 μg of venom produced IL-6, IL-10, INF-γ, TNF-α and NO in the serum. In vitro the cells from the mice injected and challenged with the venom only released IL-10 while peritoneal macrophages released IL-10, INF-γ and less amounts of IL-6; (c) establishment of local inflammation and necrosis induced by the venom, coincides with the peaks of TNF-α, IFN-γ and NO and the damage was neutralized when the venom was incubated with a monoclonal antibody against a 60 kDa haemorrhagic factor. These results suggest that susceptibility to Bothrops a trox venom is genetically dependent but MHC independent; that IL-6, IL10, TNF-α, IFN-γ and NO can be involved in the mediation of tissue damage; and that the major venom component inducers of the lesions are haemorrhagins.